Recent research in mechanical properties of geopolymer-based ultra-high-performance concrete: A review - G. Murali (Defence Technology, 2024)
Due to the growing need for sustainable and ultra-high-strength construction materials, scientists have created an innovative ultra-high-performance concrete called Geopolymer based ultra-high-performance concrete (GUHPC). Besides, in the last few decades, there have been a lot of explosions and ballistic attacks around the world, which have killed many civilians and fighters in border areas. In this context, this article reviews the fresh state and mechanical properties of GUHPC. Firstly, the ingredients of GUHPC and fresh properties such as setting time and flowability are briefly covered. Secondly, the review of compressive strength, flexure strength, tensile strength and modulus of elasticity of fibrous GUHPC. Thirdly, the blast and projectile impact resistance performance was reviewed. Finally, the microstructural characteristics were reviewed using the scanning electron microscope and X-ray Powder Diffraction. The review outcome reveals that the mechanical properties were increased when 30% silica fume was added to a higher dose of steel fibre to improve the microstructure of GUHPC. It is hypothesized that the brittleness of GUHPC was mitigated by adding 1.5% steel fibre reinforcement, which played a role in the decrease of contact explosion cratering and spalling. Removing the need for cement in GUHPC was a key factor in the review, indicating a promising potential for lowering carbon emissions. However, GUHPC research is still in its early stages, so more study is required before its full potential can be utilized.